2017
DOI: 10.21873/anticanres.12054
|View full text |Cite
|
Sign up to set email alerts
|

Pirarubicin, an Anthracycline Anticancer Agent, Induces Apoptosis Through Generation of Hydrogen Peroxide

Abstract: Abstract. Background/Aim: Pirarubicin (THP)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Therefore, these observations can be explained by the mediation of H 2 O 2 production in the apoptotic mechanism induced ACR. Our previous reports have shown that doxorubicin and pirarubicin induce oxidative DNA damage by H 2 O 2 production, followed by mitochondrial dysfunction and subsequent activation of caspase-3/7, resulting in apoptosis (16,24). Therefore, these observations show the possibility that oxidative DNA damage by H 2 O 2 production induces apoptosis.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Therefore, these observations can be explained by the mediation of H 2 O 2 production in the apoptotic mechanism induced ACR. Our previous reports have shown that doxorubicin and pirarubicin induce oxidative DNA damage by H 2 O 2 production, followed by mitochondrial dysfunction and subsequent activation of caspase-3/7, resulting in apoptosis (16,24). Therefore, these observations show the possibility that oxidative DNA damage by H 2 O 2 production induces apoptosis.…”
Section: Discussionmentioning
confidence: 62%
“…HP100 cells have approximately 340-fold higher resistance to H 2 O 2 (14) and 18 times higher catalase activity (15) than HL-60 cells. By use of HP100 cells, effects of intracellular catalase can be evaluated (16). HL-60 and HP100 cells were grown in RPMI 1640 (FUJIFILM Wako Pure Chemical Co.) supplemented with 6% fetal bovine serum (Biowest Co., Nuaillé, France) at 37˚C under 5% CO 2 in a humidified atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…In both cases, doxorubicin-induced ROS production is likely to set off an apoptotic cascade in heart cells [19]. In this fashion, as is the case for mammalian endothelial cells [15], as well as a variety of human tumor cell lines [18,37], it is the production of H 2 O 2 by doxorubicin (a process modulated by the GSHPx that is present in both cytosol and mitochondria) that plays a critical role in the initiation of cardiac apoptosis. It has been demonstrated previously, furthermore, that a doxorubicin-induced peroxide flux in mammalian cells precedes the loss of mitochondrial membrane permeability that is an initiating event in anthracycline-related activation of the apoptotic cascade [18].…”
Section: Discussionmentioning
confidence: 99%
“…Combined with free tubulin, tubulin can form stable microtubules to inhibits microtubule depolymerization, ultimately inhibiting the mitosis and proliferation of cells, and the drug also has certain effects of inducing apoptosis of tumor cells. Pirarubicin is an anthracycline cell cycle non-specific anti-tumor drug that can be directly inserted between DNA double strands to inhibits DNA polymerase,20 prevent nucleic acid synthesis, and prevent cells from dividing in G2 phase, finally leading tumor cell to death. It is also effective for those who are resistant to doxorubicin.…”
Section: Discussionmentioning
confidence: 99%